La migración del campo a la ciudad y la amplitud del vocabulario de los niños peruanos a los 8 años de edad - Vásquez Bendezú, María Cristina (2016)
This study aims to identify if migrating to cities influences linguistic development of eight-year-olds born in Peruvian rural areas. Participants of the study belong to a longitudinal sample, which provides information on their development since they were 6 months old. A linear multiple regression is performed with this information to identify related factors to vocabulary development. It was found that migration to urban areas is a significant predictor of a greater receptive vocabulary, measured by the Peabody Picture Vocabulary Test. Specifically, results show that children migrating to cities before age 5 are more likely to have greater vocabulary at age 8, than those who migrated after age 5. The children who remained living in rural areas obtained the lowest vocabulary scores. Regarding individual and contextual variables here studied, findings are similar to those from previous studies about vocabulary development. Rural-urban migration as predictor of vocabulary amplitude is a variable with no previous evidence in Peru, which is why this study provides more information for understanding the importance of contextual factors in child development, taking into consideration Bronfenbrenner’s ecological theory (1987). Therefore, it is expected that results from this study might help in the development of projects that focus on migrating children as well as on rural areas as a context that should be empowered to provide better opportunities for Peruvian children.